The presence of Superfund sites as a determinant of life expectancy in the United States - Amin Kiaghadi; Hanadi S. Rifai; Clint N. Dawson (Nature Communications, 2021)
Superfund sites have hazardous wastes that could affect the health of those who live near them, but this has not been assessed across the USA. Here the authors find that proximity to superfund sites decreases life expectancy and is further exacerbated by sociodemographic and climate change factors.